Ensaio clínico randomizado da efetividade da analgesia cirúrgica do bloqueio costoclavicular guiado por ultrassonografia para procedimentos de cotovelo, antebraço, punho e mão - Silva, Grazielle Rodrigues (2021)
Introduction: Costoclavicular block (CCB) has been described as safe and effective for surgical procedures in the elbow, forearm, wrist and hand. However, few studies have described the behavior of this technique in anesthetic practice. This randomized clinical trial compares the BCC technique with the supraclavicular combined with axillary (BSA) technique guided by ultrasound (USG) for surgical procedures of the upper limb distal to the elbow. Objectives: To compare the BCC technique with the BSA, guided by USG, for surgical procedures in the elbow, forearm, wrist and/or hand, in relation to anesthetic effectiveness, block latency, adverse events and time of execution of the anesthetic technique. Methods: The study participants were randomly assigned to two groups of equal number, where group 1 was submitted to the BSA and group 2 to the BCC. In both, ropivacaine 0.5% volume of 40ml was used. The blocks were performed by four anesthesiologists trained in both techniques. Next, researchers who were unaware of the group evaluated the dermatomes referring to the musculocutaneous, radial, ulnar and median nerves every 5 minutes, until the loss of thermal sensation to the cold was recorded, and 30 minutes after the block, loss of mobility, pain and touch in the same dermatomes. The time to perform the blockade, number of needle repositioning and the presence of adverse events were also evaluated. Results: Fifty-three people completed the study, 26 in the BSA group and 27 in the BCC group. The BCC group had shorter time to perform the needle blocking and repositioning compared to the BSA group (p <0.05). For the adverse events observed in the study, there was no difference between the groups. The proportion of complete sensory block in all studied dermatomes after 5 minutes was lower in the BCC group (29.6%, vs 57.7%, p <0.05). At 20 minutes, the complete sensory block was equivalent between the groups (96.3% vs 96.1%, p = 0.98). In the evaluation of motor block, tactile and painful sensitivity after 30 minutes, no difference was found between the techniques employed (p> 0.05). Conclusion: The BCC was similar in effectiveness to the BSA, with the advantages of being quickly performed and with less needling.